Glifosato e seus efeitos sobre duas espécies de anfíbios nativos da América do Sul Physalaemus cuvieri e Physalaemus gracilis - Herek, Jéssica Samara (2017)
Agricultural expansion and consumption of agrochemicals in particular of the herbicide Glyphosate have increased in alarming values in Brazil and worldwide. In relation to this arises a great concern about how non-target animals are affected by these chemicals. Among the vertebrates that have been most threatened by agrochemicals are amphibians, which due to their physiology and life habits are susceptible to aquatic contamination, and have been facing decline in the number of species in the last decades. The present study evaluated the acute and chronic effects (toxic and genotoxic) of a commercial formulation of Glyphosate on two species of tadpole of native anuran amphibians from South America Physalaemus cuvieri and Physalaemus gracilis. The tadpoles were submitted to concentrations that are environmentally relevant and allowed by Brazilian legislation. From morphological analyzes it was verified that Glyphosate caused morphological changes mainly in the mouth, intestine, tail, limbs, besides problems in the development of the tadpoles, as minor tadpoles and with metamorphosis delays. In the genotoxicity test, the caused a change in the frequency of formation of Micronuclei and other significant Erythrocyte Nuclear Abnormalities (ENAs) compared to the control, indicating genotoxic damages. This study shows that environmentally relevant concentrations of glyphosate in short periods of time are capable of causing morphological and erythrocyte abnormalities in both species studied.